2022
DOI: 10.1111/ajt.16835
|View full text |Cite
|
Sign up to set email alerts
|

Donor-derived cell-free DNA levels predict graft injury in liver transplant recipients

Abstract: Donor‐derived cell‐free DNA (dd‐cfDNA) has been evaluated as a rejection marker in organ transplantation. This study sought to assess the utility of dd‐cfDNA to diagnose graft injury in liver transplant recipients (LTR) and as a predictive biomarker prior to different causes of graft dysfunction. Plasma from single and multicenter LTR cohorts was analyzed for dd‐cfDNA. Phenotypes of treated biopsy‐proven acute rejection (AR, N = 57), normal function (TX, N = 94), and acute dysfunction no rejection (ADNR; N = 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 66 publications
(145 reference statements)
6
44
1
Order By: Relevance
“…Patients were initially divided into three groups: transplant excellent (TX representing IQ and healthy graft function; n = 25), acute dysfunction no rejection (ADNR, representing nonrejection causes of graft injury; n = 25), and AR ( n = 25). The AR and ADNR phenotypes were diagnosed by needle biopsy, and TX by clinical and laboratory criteria, as previously described ( 31 34 ). The absence of biopsies in TX was a limitation; however, transplant centers do not generally perform surveillance biopsies in LTR with healthy graft function.…”
Section: Bpa and Peripheral Blood Mononuclear Cells From Liver Transp...mentioning
confidence: 99%
“…Patients were initially divided into three groups: transplant excellent (TX representing IQ and healthy graft function; n = 25), acute dysfunction no rejection (ADNR, representing nonrejection causes of graft injury; n = 25), and AR ( n = 25). The AR and ADNR phenotypes were diagnosed by needle biopsy, and TX by clinical and laboratory criteria, as previously described ( 31 34 ). The absence of biopsies in TX was a limitation; however, transplant centers do not generally perform surveillance biopsies in LTR with healthy graft function.…”
Section: Bpa and Peripheral Blood Mononuclear Cells From Liver Transp...mentioning
confidence: 99%
“…Based on these results, it is expected that ctDNA will also be introduced as an efficacy indicator for ICI used before and after liver transplantation for HCC. Similar to kidney transplant acute rejection, dd-cfDNA can also be used to evaluate allograft tolerance in liver transplant recipients [ 74 , 75 ]. Levitsky et al [ 75 ] reported that the area under the curve of dd-cfDNA in the acute rejection group (n=57) compared to the normal function group (n=94) was as high as 0.95, and dd-cfDNA decreased alongside normalization after treatment for acute rejection.…”
Section: Posttransplant Cancer and Immune Checkpoint Inhibitors: A Li...mentioning
confidence: 99%
“…Similar to kidney transplant acute rejection, dd-cfDNA can also be used to evaluate allograft tolerance in liver transplant recipients [ 74 , 75 ]. Levitsky et al [ 75 ] reported that the area under the curve of dd-cfDNA in the acute rejection group (n=57) compared to the normal function group (n=94) was as high as 0.95, and dd-cfDNA decreased alongside normalization after treatment for acute rejection. Therefore, dd-cfDNA may become a biomarker for evaluating rejection in liver transplant patients who receive ICI treatment.…”
Section: Posttransplant Cancer and Immune Checkpoint Inhibitors: A Li...mentioning
confidence: 99%
“…The over-arching hypothesis is that dd-cfDNA levels above baseline may indicate graft injury; they have been associated with elevated liver enzymes in the setting of acute rejection. Longitudinal trajectories of rising dd-cfDNA levels have been linked to graft injury, and a dd-cfDNA threshold has been suggested to differentiate allo-immune attack from other mechanisms of graft injury [3]. Imaging modalities including ultrasound elastography, acoustic radiation impulse frequency imaging, or magnetic resonance elastography can be used to measure liver stiffness, which varies with the degree of inflammation, edema, and/ or fibrosis.…”
Section: Non-invasive Biomarkersmentioning
confidence: 99%